Arte-educação: uma proposta metodológica para o ensino médio - Eduardo Mosaner Jr.; Mônica Piccione Gomes Rios (EccoS – Revista Científica)
This article is the result of a research about teaching methodology of arts in high school presenting a new paradigm for the lessons of that discipline. The objective of this research was to apply the triangular proposal, enunciated by Ana Mae Barbosa, aimed at developing skills for assessment, contextualization and elaboration of poetic proposals by high school students. The theoretical framework has had as reference the triangular approach, based on three components: read (criticism and esthetics), context (art history) and do (art education). The methodology used was qualitative, descriptive and exploratory, using as a theoretical basis the action research. The students produced poetic responses in visual arts, reinterpreting and giving new interpretations to the origi - nal works based on the reading, analysis and contextualization of works from the collec - tion of the São Paulo State Art Gallery.